1992
DOI: 10.1016/0048-9697(92)90037-s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological studies on the recent seal virus epizootics in Europe and Siberia

Abstract: The virus epizootics which occurred in seals in both Europe and Siberia during 1987/1988 were caused by two different morbilliviruses, referred to as phocid distemper virus (PDV) 1 and 2, respectively. Molecular and serological studies have shown that the European virus is quite distinct from canine distemper virus (CDV), its closest relative in the morbillivirus group. Analysis of tissues obtained from infected seals from a wide geographical distribution over Northern Europe showed that the infectious agent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Between 1988 and 1993, grey and harbour seals from the Dutch Wadden Sea were found to be seropositive for PDV [30]. Similar results were obtained for the grey seals from the British Farne Island in 1992 [1]. Whether these findings indicate a persistent infection or are residuals from the 1988 epidemic remained undetermined.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Between 1988 and 1993, grey and harbour seals from the Dutch Wadden Sea were found to be seropositive for PDV [30]. Similar results were obtained for the grey seals from the British Farne Island in 1992 [1]. Whether these findings indicate a persistent infection or are residuals from the 1988 epidemic remained undetermined.…”
supporting
confidence: 72%
“…The length of the PCR product corresponded to a 364-bp band. For identification of morbillivirus RNA, a set of universal morbillivirus primers was used [1]. The expected amplicon length is 429 bp.…”
mentioning
confidence: 99%
“…Samples taken from harbour seals in 1988 from Ireland, Denmark, and the Netherlands indicated that PDV was genetically identical among affected regions (Visser et al 1990, Barrett et al 1992. A comparison of the PDV isolates from 1988 and 2002 showed the strains to be almost identical (Jensen et al 2002).…”
Section: Morbilliviruses In Marine Mammalsmentioning
confidence: 99%
“…It was concluded that PDV-2 was actually a strain of CDV, indicating that this event was unrelated to the north European outbreak in 1988 (Osterhaus et al 1989, Visser et al 1990, Barrett et al 1992). In the spring of 1997 and 2000, mass deaths of Caspian seals occurred and the cause was diagnosed as a different CDV strain (Mamaev et al 1995, Barrett 1999, Hall et al 1999, Kennedy et al 2000.…”
Section: Linkage To Terrestrial Carnivoresmentioning
confidence: 99%
See 1 more Smart Citation